Predicting obstructive sleep apnea using the STOP-Bang questionnaire in the general population - Tan, Adeline; Yin, Jason D.C.; Tan, Linda W.L.; van Dam, Rob M.; Cheung, Yan Yi; Lee, Chi-Hang (Sleep medicine, 2016)
The STOP-Bang questionnaire was developed as a quick and simple screening tool for obstructive sleep apnea (OSA) in preoperative clinics. We aimed to evaluate the validity of the STOP-Bang questionnaire to predict moderate-to-severe and severe OSA in the general population. A sample of 242 subjects selected from a population-based cohort in Singapore completed home-based sleep testing with a type 3 monitor. Subjects were asked to complete the STOP questionnaire while body mass index (BMI), age, neck circumference, and sex were recorded. A score of ≥3 on the questionnaire indicated high risk of OSA. A total of 68 subjects (28.1%) and 26 subjects (10.7%) had an apnea−hypopnea index (AHI) of ≥15 and ≥30 events per hour, respectively. Of the subjects, 89 (36.8%) were classified as high risk based on the questionnaire. The sensitivity of a STOP-Bang score of ≥3 was 66.2% to detect AHI ≥15 and 69.2% to detect AHI ≥30. The specificities were 74.7% and 67.1%, respectively. The negative predictive values were 85% for moderate-to-severe OSA and 94.8% for severe OSA. The corresponding positive predictive values were 50.6% and 20.2%, respectively. Using BMI cutoffs of 30 and 27.5 for Asians compared to the original cutoff of 35 did not improve the questionnaire performance significantly. The STOP-Bang questionnaire can be used as a screening tool in the general population in view of its moderate sensitivity and high negative predictive value for subjects with moderate-to-severe and severe OSA. The cutoff of BMI >35 can be used in Asians, as lower BMI cutoffs did not improve questionnaire performance. •The STOP-Bang questionnaire was designed as a screening tool for obstructive sleep apnea (OSA) in the preoperative clinics.•A moderate sensitivity and high negative predictive value of STOP-Bang to detect OSA in the general population were found.•Using lower body mass index cutoffs did not improve the performance of STOP-Bang in a multiethnic Asian population.